Електронна форма обліку успішності студентів - Бабенко, В.М. (Таврический медико-биологический вестник, 2012)
В условиях перехода стоматологического факультета на обучение согласно требованиям
кредитно-модульной системы для оптимизации контроля успешности студентов 2 курса на кафедре
терапевтической стоматологии разработан и внедрен электронный журнал. Такая электронная форма
контроля позволяет оперативно и всесторонне проводить анализ успеваемости, обеспечивает
прозрачность оценивания и способствует повышению ответственности студентов за результаты
учебы. In the course of transition of DMA Stomatological Department to the Bologne credit-module educational
pattern, at the Chair of Therapeutic Stomatology there has been worked out and introduced the Electronic
Register. Its purpose is to achieve the optimum effect of the control of the students’ study progress. The
electronic form of control allows to timely and comprehensively analyse the study progress of the students
and to ensure transparency of their rating. It also promotes the growth of the students’ responsibility for the
results of their studies.